Numerical investigation of the cluster property and flux distribution in three-dimensional full-loop circulating fluidized bed with multiple parallel cyclones - Yang, Shiliang (2021)
Circulating fluidized beds have been widely utilized in many industrial applications due to their excellent heat and mass transfer performance. By means of computational fluid dynamics coupled with discrete element method, numerical simulation of the three-dimensionalfull-loop circulating fluidized bed with six parallel cyclones is conducted, with a focus on the cluster behavior, flux and granular temperature. The results agree with past studies that the particle clusters dynamically evolve with time and space, and the upward-rising and downward-falling clusters tend to be in respectively the central core and near-wall regions. Notably, the frequency distribution of the cluster volume is shown to be approximately normal; and the aspect ratios of the clusters are consistently larger than one, and tend to increase before decreasing with riser height. Furthermore, the slip velocity is the most significant in the cross-sectional center of the riser and upper part of the cyclone. Finally, the granular temperatures are greatest at the cross-sectional center of the riser inlet, at the top of four of the six cyclones, and also at the middle one-third portion of the standpipe height. Moreover, the granular temperature of the solid phase increases with solid concentration in the dilute regions, but decreases with solid concentration in the dense regions. The results obtained provide insights regarding the important aspects in the CFB with multiple cyclones.